2021
DOI: 10.3389/fonc.2020.595524
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CISD2 Has Prognostic Value in Non-Small Cell Lung Cancer and Inhibits the Tumorigenesis by Inducing Mitochondrial Dysfunction

Abstract: CISD2, a NEET protein that coordinates 2Fe-2S clusters through its CDGSH domain, is critical for normal development and iron homeostasis. CISD2 plays an important role in Fe-S cluster transfer and promotes cancer proliferation. However, its specific role in the development of non-small cell lung cancer (NSCLC) remains unclear. Bioinformatics of pan-cancer analysis from The Cancer Genome Atlas show that CISD2 has an aberrant expression in most types of human cancers. Moreover, CISD2 expression is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…1; [27]) is driving the accumulation of iron in aging cardiomyocytes and that this process is accompanied by elevated expression of TfR (that subsides by 55 weeks of age). In contrast, the absence of CISD2 in cardiomyocytes from young mice could drive an active process of iron uptake, similar to the processes observed in different cells upon iron starvation, or in cancer cells that actively accumulate iron [16,17,37,52,57,58]. Because we did not analyze the expression of TfR and ferritins in cardiomyocytes during different stages of the aging process, we cannot determine whether the mechanisms of iron accumulation found in cardiomyocytes from old and young CISD2‐ KO mice are similar.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…1; [27]) is driving the accumulation of iron in aging cardiomyocytes and that this process is accompanied by elevated expression of TfR (that subsides by 55 weeks of age). In contrast, the absence of CISD2 in cardiomyocytes from young mice could drive an active process of iron uptake, similar to the processes observed in different cells upon iron starvation, or in cancer cells that actively accumulate iron [16,17,37,52,57,58]. Because we did not analyze the expression of TfR and ferritins in cardiomyocytes during different stages of the aging process, we cannot determine whether the mechanisms of iron accumulation found in cardiomyocytes from old and young CISD2‐ KO mice are similar.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies revealed that different cell types with reduced CISD2 or CISD1 expression accumulate high levels of iron in their mitochondria and display enhanced expression of TfR and ferritin [54,58,63]. This process is also accompanied by the activation of apoptosis, autophagy, and ferroptosis [16,33,50,54,57,58,64,65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hepatocellular carcinoma, the expression of CISD2 is associated with advanced clinicopathological characteristics, such as tumor size, number of tumors, surgical margin, recurrence, and poor prognosis [ 13 ]. Shao et al [ 41 ] revealed that CISD2 could be developed as a chemotherapeutic target in human breast cancer owing to its effect on cell proliferation. And Sun et al [ 14 ] reported that CISD2 was significantly increased in glioma tissues and could promote cell proliferation by inhibiting beclin-1-mediated autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several iron−sulfur proteins have been identified associated with ferroptosis [ 23 , 24 ]. Other studies also found that MitoNEET and NAF-1 play a vital role in the pathology of obesity, diabetes, heart disease, neurodegeneration, and cancer progression [ 17 , 25 , 26 ]. Limited information has been published on the homologous protein CISD3, which harbors one [2Fe−2S] cluster within a single polypeptide chain.…”
Section: Discussionmentioning
confidence: 99%